PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, MOTIVASI DAN PELIMPAHAN WEWENANG TERHADAP KINERJA MANAJERIAL DINAS DAERAH KABUPATEN KEPULAUAN SIAU TAGULANDANG BIARO - Marthin, Titien; Saerang, David Paul Elia; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2013)
The aim of this research is to test the effect of participation in budgeting, motivation, and delegation of authority towards performance managerial at the Regency of Siau Tagulandang Biaro Island. The general problem in this study is the lack of participation in budgeting, motivation and delegation of authority thus affecting the managerial performance at Regency of Siau Tagulandang Biaro Island. The population of this research are the 3rd and 4th echelon as much as 54 respondents. Multiple regression analysis by Statistical Product and Service Solution (SPSS). Independent variables in this research are participation in budgeting (X1), motivation (X2), and delegation of authority (X3), and dependent variable is performance managerial at The Regency of Siau Tagulandang Biaro Island. Before hypothesis testing with F-test and t-test, it was done instrument testing covering validity test, reliability test, classical assumptions test, multicolinearity test, normality test, heteroscesdastisity test. The study results that motivation within budgeting have a significant and positive impact on managerial performance, while the participation and delegation of authority did not significantly affect the managerial performance at Regency of Siau Tagulandang Biaro Island.